POLITICIAN'S LINGUISTIC PERSONALITY AS KEY FIGURE OF INSTITUTIONAL DISCOURSE - Sedykh, Arkadiy; Ivanishcheva, Olga; Sidorova, Tatyana; Bolgova, Elena; Bolgova, Natalia (Revista Inclusiones, 2020)
The article deals with the approaches to studying a politician's linguistic personality. The communicative potential of the manifestation means of a politician's personality is analyzed. The authors present the algorithm of studying the characteristics of an institutional linguistic personality. The foundation of identifying the essential characteristics of a linguistic personality is the linguocognitive approach that takes into account the complex parameters of a politician's speech. A politician's discourse is studied based on the interpretational analysis of the utterance. In light of the anthropocentric concept, systemic discourse means are linguistically interpreted. As an integral part of the spiritual culture, the institutional discourse, while being universal, reveals specific traits of verbalization in different languages. These traits are caused by the subjective nature of interpreting the world inherent in speakers which is undoubtedly of interest to linguistics. A hypothesis is set forth that the semantic of linguistic units with the institutional component reflects the attitude of any linguistic culture to fundamental concepts of being and thinking, and the methods of political verbalization can be interpreted as elements of a nation's linguistic self-identification. The prospects of the study appear to lie in the development of new synergetic cognitive and communicative approaches to studying linguistic units with an institutional component.